Tracking adenovirus genomes identifies morphologically distinct late DNA replication compartments. (3rd October 2016) - Komatsu, Tetsuro; Robinson, Derrick R.; Hisaoka, Miharu; Ueshima, Shuhei; Okuwaki, Mitsuru; Nagata, Kyosuke; Wodrich, Harald
Abstract : In adenoviral virions, the genome is organized into a chromatin‐like structure by viral basic core proteins. Consequently viral DNAs must be replicated, chromatinized and packed into progeny virions in infected cells. Although viral DNA replication centers can be visualized by virtue of viral and cellular factors, the spatiotemporal regulation of viral genomes during subsequent steps remains to be elucidated. In this study, we used imaging analyses to examine the fate of adenoviral genomes and to track newly replicated viral DNA as well as replication‐related factors. We show de novo formation of a subnuclear domain, which we termed Virus‐induced Post‐Replication (ViPR) body, that emerges concomitantly with or immediately after disintegration of initial replication centers. Using a nucleoside analogue, we show that viral genomes continue being synthesized in morphologically distinct replication compartments at the periphery of ViPR bodies and are then transported inward. In addition, we identified a nucleolar protein Mybbp1a as a molecular marker for ViPR bodies, which specifically associated with viral core protein VII. In conclusion, our work demonstrates the formation of previously uncharacterized viral DNA replication compartments specific for late phases of infection that produce progeny viral genomes accumulating in ViPR bodies. Abstract : The spatial relationship between early adenoviral genome replication and subsequent viral gene expression has been established. In contrast, when and where newly replicated genomes are linked to progeny virion production remains unclear. Using direct genome‐labeling techniques, we show the formation of a novel subnuclear compartment late in infection, which we named Virus‐induced Post‐Replication (ViPR) body that functions as a reservoir for replicated adenoviral genomes, and identified a host factor specifically localizing in the domain. The potential role of ViPR bodies is discussed.